Оrganizational Change as “Push Factor” of Employees’ Turnover Intention: Statistical Analysis of the Employees in the Republic of North Macedonia - Ristovska, Andrijana; Eftimov, Lјupcho (Ss. Cyril and Methodius University in Skopje, Faculty of Economics-Skopje, 2021)
The process of globalization and intensive technological development imposes the need to constantly introduce different types of organizational changes. Human resource managers in organizations are becoming increasingly aware that hiring and retaining talents are the most important determinants of success in the complex global world and that they must work more intensively on modernizing the process of change management to help employees, not only for acceptance, but also for their involvement in the change implementation process. This paper analyzes the impact of four different types of organizational change on employee turnover intention, according to the Cummings and Worley (2014) organizational change classification. The statistical method of simple linear regression was applied to predict and evaluate the turnover intention of the employees in the Republic of North Macedonia (as a dependent variable “Y”) based on the value of each of the types of organizational changes (as independent variables “X”). A multiple regression method was also applied in order to analyze the associations between the independent variables and the dependent variable and identify the type of organizational changes that most significantly affects the employee turnover intention. The analysis was conducted based on the findings obtained from the respondents who completely answered the survey questionnaire (282 employees in the Republic of North Macedonia, different according to their demographic characteristics). The correlation analysis shows there are positive correlation as well as causal relationship between all four types of organizational changes and the employee turnover intention, where techno-structural interventions have the most significant impact.
Keywords: organizational changes, human process changes, techno-structural changes, human resource management changes, strategic changes, turnover intention.